MORPHOBIOCHEMICAL FUNCTIONS OF THE SHEEP ORGANISM AND THEIR ADJUSTMENT IN THE CONDITIONS OF IODINE DEFICIENCY - M. I. Selionova; A. K. Mikhailenko; L. N. Chizhova; C. B. Chotchaeva; E. S. Surzhikova (Юг России: экология, развитие)
Aim. Widespread iodine deficiency causing endemic diseases in the highlands of the North Caucasus relate to the iodine epidemic. This type of pathology causes economic damage to the livestock industry, including sheep. In this regard, the aim of this work was to study morphobiochemical changes, hormonal (thyroid) background, immune reactivity in Karachai sheep during ontogenesis in different ecological zones with different iodine availability levels as well as to consider the effect of exogenous hormone (thyroxine) on the immune status of young stock under conditions of iodine deficiency and determine promising ways of developing an effective method of prevention and treatment against the pathology.Methods. We conducted an analysis of the blood of lambs aged 1, 2, 3, 4 and 8 months kept in conditions of unequal iodine provision. The serum concentration of thyroid hormones (T3, T4) was evaluated by the results of an enzyme immunoassay, morphobiochemical status and immune reactivity by hematological, biochemical analysis, correction of iodine deficiency by intramuscular injections of thyroxine at a dose of 1 mg/kg with an interval of 2-3 months.Results. The ontogenetic features of the formation of morphobiochemical systems, hormonal background, immune status in sheep kept in different climatic zones with different iodine provision were established.Conclusion. Disorders of hematopoietic function, differences in hematological parameters, hypoproteinemia, changes in hormonal levels, low levels of immunocompetent T and B cells in the blood of sheep from different zones were detected. It was established that the metabolic response to exogenous thyroxine contributed to the normalization of metabolic processes and activation of cellular immunity.